(3eMGVQI GdChGFd heSGaQI GdChGFds - (3GdehSJGQj, Ke GdScJhGQj, , YdGA GdOjf, Ydj OOg, TjN GdJQHI, Ydj Hf eUWai, J (B1007 (3g`s ((3CeQ Gddg GdHhSfhjs)
(3ChdgG (B:s
(3jG Chd HdG HOGjI hjG BNQ HdG fgGjI dc GdMeO ChdG (B... (3deG GWdYJ Ydi cJGH dWja aj GdChGFd ddEeGe LdGd GdOjf GdSjhWj dNUJg HMPa GdCSGfjO hGdRhGFO hCSeGA GdcJH GdefbhdI YfgG HfGkA Ydi GdCUd (B...s
(3BNQgG (B:s
(3GdaUd GdQGHY ef GdbSe GdKGfj (B...(3BNQ ef cGf cdGeg dG Edg EdG Gddg ONd GdLfI (B, (3EP hQO aj GdMOjK GdUMjM Yf QShd Gddg Udi Gddg JYGdi Ydjg hSde ef cGf BNQ cdGeg (B...(3hHg Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\287s
(3cTa GdXfhf (B2\1610s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdeYGQa GdYGeIs